Europium coordination compounds based on carbacylamidophosphate ligands for metal-organic light-emitting diodes (MOLEDs) - Litsis, O.O.; Ovchynnikov, V.A.; Sliva, T.Yu.; Amirkhanov, V.M.; Sorokin, V.M.; Minyailo, M.A.; Kolomzarov, Yu.V.; Tytarenko, P.A.; Minakova, I.E. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2013)
In this work, the photo- and electroluminescence properties of new red
phosphores based on europium complexes with carbacylamidophosphate (CAPh) ligands
and additional aromatic ligands 1,10-phenantroline and 4,4'-bipyridine have been
studied. Compounds Eu(L¹)₃(phen) (1), Eu(L²)₃(phen) (2), Eu2(L¹)₆(i-prOH)²(4,4'-bipy)
(3) and Eu²(L²)₆(H2O)²(4,4'-bipy) (4), where HL – 2,2,2-trichloro-N-(dipiperidin-1-ylphosphoryl) acetamide,
HL² – 2,2,2-trichloro-N-(dimorpholin-1-ylphosphoryl)acetamide,
were synthesized. Technology of europium complexes coating
from solutions with different concentrations in different solvents has been developed.
Experimental samples of light-emitting planar heterostructures were fabricated using the
device architecture comprising an anode (ITO), a hole transport layer of 1,4-
Bis(diphenylamino)benzene (BDB), a layer of complex and a cathode (Al or Mg).
Another heterostructure configuration with a hole-transport layer of poly(3,4-
ethylenedioxythiophene) poly(styrenesulfonate) (PEDOT:PSS) has also been
investigated. The different types of planar heterostructures were prepared, and their
current-voltage characteristics have been discussed.